Ground-based detection of G star superflares with NGTS. Issue 4 (10th April 2018) - Jackman, James A G; Wheatley, Peter J; Pugh, Chloe E; Gänsicke, Boris T; Gillen, Edward; Broomhall, Anne-Marie; Armstrong, David J; Burleigh, Matthew R; Chaushev, Alexander; Eigmüller, Philipp; Erikson, Anders; Goad, Michael R; et al.
Abstract: We present high cadence detections of two superflares from a bright G8 star ( V = 11.56) with the Next Generation Transit Survey (NGTS). We improve upon previous superflare detections by resolving the flare rise and peak, allowing us to fit a solar flare inspired model without the need for arbitrary break points between rise and decay. Our data also enables us to identify substructure in the flares. From changing star-spot modulation in the NGTS data, we detect a stellar rotation period of 59 h, along with evidence for differential rotation. We combine this rotation period with the observed ROSAT X-ray flux to determine that the star's X-ray activity is saturated. We calculate the flare bolometric energies as $5.4^{+0.8}_{-0.7}× 10^{34}$ and $2.6^{+0.4}_{-0.3}× 10^{34}$ erg and compare our detections with G star superflares detected in the Kepler survey. We find our main flare to be one of the largest amplitude superflares detected from a bright G star. With energies more than 100 times greater than the Carrington event, our flare detections demonstrate the role that ground-based instruments such as NGTS can have in assessing the habitability of Earth-like exoplanets, particularly in the era of PLATO .